Impact of Workplace Diversity in Nepalese Organizations - Khatri, Rabina (Nepalese Journal of Management, 2025)
This study examines the impact of workplace diversity in Nepalese organizations. Organizational performance is selected as the dependent variable. Similarly, age diversity, gender diversity, ethnic diversity, educational background diversity and marital status diversity are selected as the independent variables. This study is based on primary data with 123 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors influencing workplace diversity in Nepalese organizations. The study showed that that age diversity has a positive impact on organizational performance. It means that increase in age diversity in organization leads to increase in organizational performance. Similarly, gender diversity has a positive impact on organizational performance. It means that increase in gender diversity in an organization leads to increase in organizational performance. Moreover, ethnic diversity has a positive impact on organizational performance. It means increase in ethnic diversity in an organization leads to increase in organizational performance. Likewise, marital status diversity has a positive impact on organizational performance. It means that increase in marital status diversity in an organization leads to increase in organizational performance. Further, educational background diversity has a positive impact on organizational performance. It implies that increase in educational background diversity in an organization leads to increase in organizational performance.